2008
DOI: 10.1097/chi.0b013e318172ef4b
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Autonomic Correlates of Conduct Problems and Aggression

Abstract: Objective To examine sex differences in autonomic nervous system functioning in children and adolescents with conduct problems and to evaluate the role of aggression in predicting autonomic nervous system functioning, over and above the effects of disruptive behavior. Although deficiencies in autonomic responding among boys with oppositional defiant disorder and/or conduct disorder are well documented, it remains unclear whether such findings extend to girls or apply only to children with aggressive forms of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
128
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(143 citation statements)
references
References 40 publications
12
128
3
Order By: Relevance
“…Second, although this sample was more heterogeneous compared with the previous study (Oliver, 2007), the sample was still predominantly female and White. As there are gender differences in cardiac reactivity (Beauchaine, Hong, & Marsh, 2008), a more diverse sample would positively effect external validity and allow generalizability to a broader population. Third, the use of rewards in the Iaboni et al (1997) study resulted in significant physiological differences between ADHD and non-ADHD children.…”
Section: Discussionmentioning
confidence: 99%
“…Second, although this sample was more heterogeneous compared with the previous study (Oliver, 2007), the sample was still predominantly female and White. As there are gender differences in cardiac reactivity (Beauchaine, Hong, & Marsh, 2008), a more diverse sample would positively effect external validity and allow generalizability to a broader population. Third, the use of rewards in the Iaboni et al (1997) study resulted in significant physiological differences between ADHD and non-ADHD children.…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation revealed that resting HR in adolescent girls aged 16–18 years was positively correlated with antisocial behaviors while in males of the same age was negatively correlated with antisocial behaviors (Crozier et al 2008). Similarly, increased electrodermal responding (a sympathetic measure) was related to increased conduct problems in females aged 8– 12 while lower baseline parasympathetic cardiovascular activity was seen in boys high in aggression (Beauchaine et al 2008). …”
Section: Gender Differencesmentioning
confidence: 95%
“…We have now examined PEP responses to monetary incentives among male externalizing preschoolers, middle-schoolers, and adolescents ranging in age from 4–18, in several separate studies (Beauchaine et al, 2001; Beauchaine, Hong, & Marsh, 2008; Crowell et al, 2006; Mead et al, 2004). These samples included individuals with ADHD, ODD, CD, and antisocial personality traits.…”
Section: Cardiac Pre-ejection Period: a Marker Of Central Da Responding?mentioning
confidence: 99%
“…In fact, in each of the studies cited above in which PEP responding to reward was assessed, RSA data were also collected. Interestingly, attenuated baseline RSA and/or excessive RSA reactivity to emotion evocation were observed only in the in conduct-disordered middle school and adolescent samples (Beauchaine et al, 2001; Beauchaine, Hong, & Marsh, 2008; Mead et al, 2004). In contrast, neither RSA nor RSA reactivity discriminated externalizing preschoolers with ADHD and ODD from controls (Crowell et al, 2006).…”
Section: Respiratory Sinus Arrhythmia and Emotion Regulationmentioning
confidence: 99%